KELEMBAGAAN DAN CAPAIAN PROGRAM KELUARGA BERENCANA (KB): DARI ERA SENTRALISASI KE DESENTRALISASI - Puri Kusuma Dwi Putri; Aida Vitayala Hubeis; Sarwititi Sarwoprasodjo (Jurnal Kependudukan Indonesia, 2019)
Indonesia experienced a change in the organization of the Family Planning (FP) Program from centralized to a decentralized one. This article aims to compare various Indonesia’s FP policies, implemented by the National Population and Family Planning Board (NPFPB), in each era of governance, and their respective Total Fertility Rate (TFR) and Population Growth Rate (PGR) achievements. We reviewed FP programs from Soekarno’s presidency until Joko Widodo’s presidency (1983-2018). The centralization approached was implemented during the Soekarno’s and Soeharto’s presidency, while the decentralization has been implemented since Habibie’s and Joko Widodo’s presidency. The centralization approach in Soeharto’s presidency had succeeded in lowering the TFR and become success story of the FP program. In contrast, the decentralization approach has not reached its target since it has impacted the organizational structure and family planning programs and their achievements through every new presidency. The decentralization also changed the communication role in the declining TFR and PGR era in each presidency in Indonesia.